Different interventions in preventing sufentanil-induced cough: a systematic review and network meta-analysis - Liu, Hao; He, Yuewen; Ding, Longfei; Zhang, Zhengze; Wu, Tong; Li, Ruogen; Wang, Yong; Ma, Wuhua (Frontiers in Pharmacology, 2025)
BackgroundSufentanil-induced cough (SIC) is prevalent in anesthesia practice. A variety of interventions have been employed to prevent SIC. However, the optimal intervention remains elusive.MethodsA comprehensive search of the literature was conducted on the PubMed, Embase, Web of Science, Cochrane Library (CENTRAL) and China National Knowledge Infrastructure (CNKI) databases. The search was limited to publications prior to July 5, 2025. A network meta-analysis (NMA) was conducted using the R software. A Bayesian framework was employed for this NMA. Comparisons of competing models based on the deviance information criterion (DIC) were used to select the optimal model for NMA. The primary outcome is the overall incidence of SIC. The secondary outcomes included the incidence of mild SIC and moderate to severe SIC.ResultsThe NMA included 37 randomized controlled trials (RCTs) with 5,105 patients and 18 interventions. Pairwise meta-analysis results indicate that the intervention group significantly decreases the overall incidence of SIC (7.6% vs. 34.8%; OR 0.13; 95% CI 0.09 to 0.18; P < 0.0001; I2 = 53.0%), the incidence of mild SIC (4.0% vs. 13.0%; OR 0.28; 95% CI 0.22 to 0.35; P = 0.369; I2 = 5.7%), and the incidence of moderate to severe SIC (3.4% vs. 21.7%; OR 0.13; 95% CI 0.10 to 0.16; P = 0.040; I2 = 30.6%). NMA results suggested that nalbuphine, dezocine, and butorphanol significantly reduced the overall incidence of SIC, as well as the incidence of mild and moderate-to-severe SIC. Additionally, remifentanil and esketamine were effective in reducing both the overall incidence of SIC and the incidence of moderate to severe SIC. The use of a mechanical dropper was also effective in reducing the incidence of moderate to severe SIC.ConclusionThree pharmacological interventions—nalbuphine, dezocine, and butorphanol significantly reduced the overall incidence of SIC, as well as the incidence of mild and moderate-to-severe SIC. Additionally, remifentanil and esketamine were effective in reducing the overall incidence of SIC and the incidence of moderate to severe SIC. The application of a mechanical dropper was also effective in reducing the incidence of moderate to severe SIC. The remaining interventions indicated a trend toward reducing SIC incidence; however, this was not statistically significant.Systematic Reviewhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024581866 , PROSPERO (CRD42024581866)